A GA/IPSO based Approach for System Loss Reduction and Voltage Profile Improvement Employing Arithmetic Crossover and Mutation - Kilonzi, Julius Charles; Abungu, Nicodemus Odero (International Journal of Engineering Science and Technology, 2013)
Reduction of system losses and improvement of voltage profile is one of the key aspects in power system operation. Though many methods are used to achieve this aspect, Distributed Generation (DG) has found increased usage nowadays due to its many advantages. Majority of algorithms proposed in this area have emphasized on real power losses only in their formulations. In modern practical power systems reactive power injection plays a critical role in voltage stability control, thus the reactive power losses need to be incorporated in optimizing DG allocation for voltage profile improvement. This paper aims at solving this problem by proposing a hybrid of GA and IPSO to optimize DG location and size while considering both real and reactive power losses. The hybrid technique aims at inheriting the good traits from the two techniques while avoiding the undesirable ones. Arithmetic crossover and mutation has being employed in the proposed algorithm.
Keywords: Distributed Generation (DG); Particle Swarm Optimization (PSO); Genetic Algorithm (GA); System loss reduction; Voltage profile improvement